Iranian Student Experience Pursuing Admission to Universities in the United States - Hefner-Babb, Theresa S.; Khoshlessan, Rezvan (Journal of International Students, 2018)
This qualitative phenomenological study investigated the challenges faced by Iranian students during the admissions process at a mid-size southern university in the United States. Researchers used a convenience sample from Iranian masters and doctoral degree applicants admitted for the 2015-2016 academic year. Using face-to-face interviews researchers collected responses from seven Iranian students currently in the first year of their graduate programs. The overarching question guiding the study concentrated on the challenges experienced by Iranian students during the university admissions process. Focused questions included a discussion of specific challenges faced by Iranian students. The results from the interviews led the researchers to common themes that resonated across all three focused questions and a student recommendation on ways to streamline the process.